Odpowiedzi

Najlepsza Odpowiedź!
2009-12-01T11:21:32+01:00
A]x³=x₂→x³-x²=0→x(x²-x)=0→x=0lub z nawiasu:Δ=b²-4ac=1+4=5,,,, √Δ=√5,,,x₂=(-b+√Δ):2a=(1+√5):2=½+√5/2,,,,x₃=(1-√5):2=½-√5/2,,,,,, b]4x⁴+4x³+x²=0→x²(4x²+4x+1)=0→x=0 lub z nawiasu:Δ=16-16=0,czyli x₂=-4:8=-½,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,, c]x³+3x²-x-3=0→x²(x+3)-(x+3)=0→x₁=0 lub x₂=-3 lub x₃=-3 ,,,,,, d]2x³-3x²-4x+6=0→x²(2x-3)-2(2x-3)=0 czyli:(x²-2)(2x-3)=0→Δ=0=4=4,√Δ=2→x₁=2:2=1,x₂=-2:2=-1,, lub 2x=3→x=1,5
2009-12-01T11:48:18+01:00
A)x³=x²
x³ - x² = 0
x²(x - 1) = 0
x² = 0 lub x - 1 =0
x = 0 lub x = 1
Pdp. x = 0 lub x = 1

b)4x⁴+4x³+x²=0
x²(4x² + 4x + 1) = 0
x² = 0 lub 4x² + 4x + 1 = 0
x = 0 lub (2x + 1)² = 0
x = 0 lub 2x + 1 = 0
x = 0 lub 2x = -1
x = 0 lub x = -½
Odp. x = 0 lub x = -½

c)3x²-x-3=0
Δ = 1 - 4*3*(-3)
Δ = 37
√Δ = √37
x₁ = (-1-√37)/6
x₂ = (-1+√37)/6
Odp. x = (-1-√37)/6 lub x = (-1+√37)/6

d)2x³-3x²-4x-6=0
2x(x² -2)-3(x² -2) = 0
(x² - 2)(2x - 3) = 0
x² - 2 = 0 lub 2x - 3 = 0
x² = 2 lub 2x = 3
x = √2 lub x = -√2 lub x = 3/2
Odp. x = √2 lub x = -√2 lub x = 3/2